Cohort profile: Anhui Maternal–Child Health Study in China - Yunxia Cao; Ruoling Chen; Weiju Zhou; Xiaofeng Xu; Xiaoqing Peng; Jiaqian Yin; Chunmei Liang; Ranjit Khutan; Fang-Biao Tao (BMJ Open)
Purpose The Anhui Maternal–Child Health Study (AMCHS) aims to examine determinants of reproduction, pregnancy and postpartum maternal and child health outcomes in Chinese women who received assisted reproductive technology (ART).Study design and participants AMCHS is an ongoing cohort study starting from May 2017. AMCHS recruits participants from all couples who sought ART treatment in the First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, China. The participants are interviewed to document baseline sociodemography, lifestyles, dietary intake and environmental exposure. Their clinical characteristics are obtained from hospital records. Samples of blood, follicular fluid and semen are collected at the clinic. Participants receive a standard long pituitary downregulation or a short protocol with an antagonist for the treatment. They are followed up from preconception to delivery, or discontinuation of ART treatment. Details of their children’s health are documented through a questionnaire focusing on developmental status and anthropometry measurement.Findings to date Until April 2021, AMCHS had recruited 2042 couples in the study. 111 women withdrew from the study and 19 failed to retrieve oocytes. Among the 1475 confirmed pregnancies, 146 had miscarriages or terminated their pregnancies, 9 had stillbirths and 263 were ongoing pregnancies. The implantation failure increased with maternal age; adjusted OR was 1.43 (95% CI 1.16 to 1.77) in the age of 31–35 years, 1.97 (95% CI 1.46 to 2.66) in 35–39 years and 6.52 (95% CI 3.35 to 12.68) in ≥40 years compared with those aged 20–30 years. Among the 1057 couples with successful ART who were followed up for delivering babies, 576 had their children examined at age 30–42 days, 459 at 6 months and 375 at 12 months.Future plans The AMCHS will identify comprehensive risk factors for poor ART outcomes and explore potential interaction effects of multiple factors including sociopsychological aspects of environmental exposure, dietary intake and genetics on maternal and child health.